Vortex Beam Ionization: A Novel Approach to Advanced Communication Systems - Goshu, Belay Sitotaw (Budapest International Research and Critics University, 2024)
The purpose of this study is to examine the vortex beams' interaction with ionized media this work centers on the kinetics of the beam's propagation and its ionization efficiency. The spatial distribution of the intensity of the vortex beam propagating through plasma, paying special attention to the energy transfer and beam waist evolution processes. It was discovered that the ionization rate was roughly 1.0 ×10-6, indicating a low ionization efficiency at the specified energy levels. Furthermore, to understand the mechanisms governing the interaction between the vortex beam and the plasma break, down the electromagnetic fields into external and induced components. The findings suggest that optimizing the beam's parameters, such as intensity and polarization, can enhance ionization efficiency and improve applications in plasma-assisted communication and advanced particle manipulation. Furthermore, understanding how the medium's properties affect vortex beam propagation is crucial for developing more efficient systems. The study highlights the importance of considering plasma characteristics when applying vortex beams to practical problems and offers recommendations for improving ionization efficiency and beam stability in ionized environments.